Dietary supplementation with Melaleuca alternifolia essential oil improves survival and resistance to Saprolegnia in tambatinga - da Silva, Maria Ildilene; Pestana, Mateus César Araújo; Marchão, Rafael Silva; Costa, Thaisa Sales [UNESP]; Baldisserotto, Bernardo; Marinho, Iara Reis; Doihara, Izumy Pinheiro; Pereira, Alécio Matos; Lopes, Jane Mello (Universidade Estadual de Londrina, 2025)
Fish diets should not only be formulated to meet nutritional needs (e.g., protein and energy), but also to prevent disease and promote health. In this regard, essential oils addition to diets of fish of commercial interest has been intensifying in recent years. This 45-day study assessed the efficacy of dietary supplementation with the essential oil of Melaleuca alternifolia (EOMA) in improving growth and survival of tambatinga (Colossoma macropomum x Piaractus brachypomus) naturally infected with Saprolegnia sp. The juveniles (10.60 ± 2.18 g; 8.46 ± 0.61 cm) were distributed into 20 150-L polyethylene tanks operated as a recirculating system under constant aeration (n=160; 8 fish/tank). The fish received diets containing one of the following EOMA concentrations: 0.0, 1.0, 1.5, 2.0, and 2.5 mL/kg feed. At the end of the trial, no statistical difference was seen between treatments regarding weight gain, specific growth rate, and condition factor. On the other hand, dietary inclusion of EOMA showed a positive linear relationship with survival rate. EOMA demonstrated antifungal efficacy, since fish mortality decreased as its concentration was raised. Incorporation of EOMA into the diet of tambatinga juveniles enhanced resistance to the pathogenic oomycete Saprolegnia sp., resulting in increased final survival rates at concentrations exceeding 1.5 mL/kg feed.
Suplementação alimentar com óleo essencial de Melaleuca alternifolia melhora a sobrevivência e a resistência à Saprolegnia em tambatinga
Keywords: Alternative supplement; Aquaculture; Health; Nutrition; Tea tree